Antioxidant properties of three banana cultivars (Musa acuminate ‘Berangan’, ‘Mas’ and ‘Raja’) extracts - Tan, Ee Shian; Aminah Abdullah; Khalid Hamid Musa; Maaruf Abd. Ghani; Mohammad Yusof Maskat (Universiti Kebangsaan Malaysia, 2012)
The effect of solvent type in antioxidant compounds extraction from banana tissues was studied. The solvent system used was pure methanol, ethanol, acetone and their aqueous solution at 50% and 70% concentrations. Comparison among three common cultivars of banana in Malaysia (Berangan, Mas and Raja) had been done and their antioxidant activities were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging system, ferric reducing ability in plasma (FRAP) assays and total phenolic content (TPC) assays. Acetone 70% had the strongest antioxidant compounds extraction power as compared to other solvent. All banana samples were found to be low in primary antioxidant but powerful secondary antioxidant source of fruit. The ascending order of banana cultivars in term of their antioxidant activities in all antioxidant assays carried out were Berangan < Mas < Raja. FRAP-TPC assays were highly correlated (R2>0.70) than FRAP-DPPH and TPC-DPPH assays due to the same mechanism that occurred in the reaction of FRAP and TPC assays